2003
DOI: 10.1128/jvi.77.19.10366-10375.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Adenovirus (Ad) Penton Base Neutralizing Epitopes by Use of Sera from Patients Who Had Received Conditionally Replicative Ad (Ad dl 1520) for Treatment of Liver Tumors

Abstract: Sera from 17 patients with primary and secondary liver tumors who had been administered oncolytic adenovirus (Ad) mutant Addl1520 were analyzed for anti-Ad neutralization titers and antibodies to the Ad major capsid proteins hexon, penton base (Pb), and fiber. The antibodies recognized mainly conformational epitopes in hexon and both linear and conformational epitopes in Pb and fiber. Pb-specific antibodies were isolated from serum samples that had been obtained prior to and during the course of the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 36 publications
1
78
0
Order By: Relevance
“…Previous studies have also shown that chimeric rAd5 vectors containing the Ad2, Ad6, or Ad12 hexon genes were able to evade a substantial fraction of anti-Ad5 immunity in rodents (20 -22), although these studies did not differentiate between the contributions of hexon-specific humoral and cellular immunity. In contrast with these reports, a recent clinical study suggested that fiber-and penton-specific Abs were in fact substantially higher titer than hexon-specific Abs in humans using Western blot analyses (23). Another clinical study similarly reported that Ad5-specific Abs recognized primarily fiber and penton determinants and that these Abs exhibited synergistic neutralizing activity (24).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Previous studies have also shown that chimeric rAd5 vectors containing the Ad2, Ad6, or Ad12 hexon genes were able to evade a substantial fraction of anti-Ad5 immunity in rodents (20 -22), although these studies did not differentiate between the contributions of hexon-specific humoral and cellular immunity. In contrast with these reports, a recent clinical study suggested that fiber-and penton-specific Abs were in fact substantially higher titer than hexon-specific Abs in humans using Western blot analyses (23). Another clinical study similarly reported that Ad5-specific Abs recognized primarily fiber and penton determinants and that these Abs exhibited synergistic neutralizing activity (24).…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, studies in rodents using hexon-chimeric viruses have suggested that hexon-specific immune responses also contribute substantially to anti-Ad5 immunity in vivo (20 -22). In contrast, recent clinical studies have reported that fiber-and penton-specific Abs were more frequent and higher titer than hexon-specific Abs in humans (23) and that fiber-and penton-specific Abs exerted synergistic neutralizing activity (24). It is clear from these studies that Ad5-specific Abs against multiple capsid components are generated.…”
Section: Neutralizing Antibodies To Adenovirus Serotype 5 Vaccine Vecmentioning
confidence: 80%
See 2 more Smart Citations
“…27 However, viral protein expression on the cell surface does not possess the same importance for adenoviruses as for other OVs as Nabs recognize viral proteins not expressed on the carrier-cell surface. 28 We performed short infection times as a measure of safeguard. In our studies, the loading time was set to 4 h, as this is the minimum amount of time necessary to infect a substantial proportion of carrier cells.…”
Section: Discussionmentioning
confidence: 99%